New genus and species of moth flies (Psychodidae: Psychodinae) from a mountainous area in the Atlantic Forest of Minas Gerais, Brazil - Cordeiro, Danilo Pacheco; Camico, Jéssica Luna (Zootaxa, 2023)
Maruinini is one of the most diverse tribes of moth flies in the Neotropical region. We describe two new species, Arisemus sinuosus sp. nov. and Neopericoma bela gen. nov. et sp. nov., collected in streams and waterfalls of a mountainous formation on the Brazilian Atlantic Forest of eastern Minas Gerais, Brazil. In contrast to the morphology of the type species of Australopericoma Vaillant, a new genus is proposed, Neopericoma gen. nov., to accommodate one new species and other eight species previously placed in Australopericoma: N. abnormalis (Quate & Brown) comb. nov., N. bulbula (Quate & Brown) comb. nov., N. cesticela (Quate & Brown) comb. nov., N. exilis (Quate & Brown) comb. nov., N. onofrei (Araújo & Bravo) comb. nov., N. pallidula (Tonnoir) comb. nov., N. roessleri (Wagner and Joost) comb. nov., N. xavierae (Araújo & Bravo) comb. nov. This is the first record of Arisemus in the State of Minas Gerais.